2003
DOI: 10.1055/s-2003-38993
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of Large Strains in Functional Tissue Engineering of Heart Valves

Abstract: The results demonstrate the significance of large strains in promoting tissue formation. This study may provide a methodological basis for tissue engineering of heart valves appropriate for systemic pressure applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(57 citation statements)
references
References 18 publications
2
55
0
Order By: Relevance
“…The application of mechanical stimulation to 3-D cultures (whether these are engineered tissues intended for regenerative medicine or simpler models intended for mechanobiology studies) is intended to mimic physiological conditions since most native tissues bear varying levels of strain, which significantly regulates their matrix composition and microstructure. Indeed, various engineered tissues such as heart valves, vascular tissues, and cartilage are commonly grown under physiologically-mimicking mechanical conditions in an attempt to achieve native tissue-like properties [9][10][11]. Similarly, collagenous matrices that have been grown under mechanical stimulation demonstrate improvements in cell alignment and collagen fibrillar orientation and packing [12].…”
Section: Introductionmentioning
confidence: 99%
“…The application of mechanical stimulation to 3-D cultures (whether these are engineered tissues intended for regenerative medicine or simpler models intended for mechanobiology studies) is intended to mimic physiological conditions since most native tissues bear varying levels of strain, which significantly regulates their matrix composition and microstructure. Indeed, various engineered tissues such as heart valves, vascular tissues, and cartilage are commonly grown under physiologically-mimicking mechanical conditions in an attempt to achieve native tissue-like properties [9][10][11]. Similarly, collagenous matrices that have been grown under mechanical stimulation demonstrate improvements in cell alignment and collagen fibrillar orientation and packing [12].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure of the tissue engineered leaflets to mechanical stimulation (cyclic strain) resulted in stronger but less pliable tissues compared with only perfused tissues, in agreement with other studies. 24 This observation indicates the positive effect of mechanical stimulation on the mechanical strength and may be related to a higher degree of cross-links among the collagen fibers. The mechanical strength of tissue engineered leaflets did not reach physiological values 4 during the investigated in vitro cultivation time period.…”
Section: Discussionmentioning
confidence: 90%
“…This may be explained by the uncompleted collagen production suggesting further improvement of the mechanical loading protocol in vitro. 24,25 This will be investigated in future studies and the functionality of the engineered tissues in vivo will have to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…No studies are known in which deformation of tissue engineered heart valves was determined in such a way. The research in literature that has been performed includes studies in which relatively simple tissue engineered constructs, 2D geometries 10,11,24 or blood vessels 22,23 instead of heart valves were subjected to preset deformational changes. Mechanical stimulation in these bioreactor systems shows strong similarity to the way load is applied by uni-or biaxial stretching devices.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an increase in ultimate tensile strength and tissue stiffness is observed, compared to static control. 21,24,28,29,38,39 In a recently developed bioreactor concept, the Diastolic Pulse Duplicator (DPD), 25 dynamic strains were induced in the heart valve leaflets by applying a dynamic pressure difference over the closed valve. The strain-based conditioning approach was tested by culturing human heart valve leaflets in vitro.…”
Section: Introductionmentioning
confidence: 99%